Investigation into the controversial association of Streptococcus gallolyticus with colorectal cancer and adenoma. - Abdulamir, Ahmed Sahib; Hafidh, Rand Riadh; Mahdi, Layla K.; Al Jeboori, Tarik R.; Abu Bakar, Fatimah (BioMed Central, 2009)
BACKGROUND:The seroprevalence of IgG antibodies of Streptococcus gallolyticus subspecies gallolyticus, CIP 105428, was evaluated to investigate the controversial association of S. gallolyticus with colorectal carcinoma and adenoma in attempt to investigate the nature of such association if any, by exploring the mRNA expression of NF-kappaB and IL-8. Moreover, the serological behavior of S. gallolyticus IgG antibodies was compared to that of an indicator bacterium of bowel, Bacteroides fragilis. METHODS:ELISA was used to measure IgG antibodies of S. gallolyticus and B. fragilis in sera of 50 colorectal cancer, 14 colorectal adenoma patients, 30 age- and sex- matched apparently healthy volunteers (HV) and 30 age- and sex- matched colonoscopically-proven tumor-free control subjects. NF-kappaB and IL-8 mRNA expression was evaluated in tumorous and non-tumorous tissue sections of carcinoma and adenoma patients in comparison with that of control subjects by using in situ hybridization assay. RESULTS:Colorectal cancer and adenoma patients were associated with higher levels of serum S. gallolyticus IgG antibodies in comparison with HV and control subjects (P < 0.05) while no similar association was found with serum IgG antibodies of B. fragilis (P > 0.05). ELISA cutoff value for the seropositivity of S. gallolyticus IgG was calculated from tumor-free control group. The expression of NF-kappaB mRNA was higher in tumorous than non-tumorous tissue sections of adenoma and carcinoma, higher in carcinoma/adenoma sections than in control subjects, higher in tumorous sections of carcinoma than in adenoma patients, and higher in S. gallolyticus IgG seropositive than in seronegative groups in both tumorous and non-tumorous sections (P < 0.05). IL-8 mRNA expression in tumorous sections of adenoma and carcinoma was higher than in non-tumorous sections, higher in carcinoma/adenoma than in control subjects, and higher in S. gallolyticus IgG seropositive than in seronegative groups in tumorous rather than non-tumorous sections (P < 0.05). CONCLUSION:S. gallolyticus most likely plays an essential role in the oncogenic progression of normal colorectal mucosa to adenoma and to CRC. This promoting/propagating role of S. gallolyticus might take place by utilizing certain inflammatory, anti-apoptotic, and angiogenic factors of transformation including NF-kappaB and IL-8.